Validity of Bartram’s Painted Vulture (Aves: Cathartidae) - Snyder, Noel F. R.; Fry, Joel T. (Zootaxa, 2013)
William Bartram described the Painted Vulture (Vultur sacra) as a new species in his 1791 book on travels in Florida and other southeastern states. However, no specimen of this bird survives, and it has not been reported by any subsequent or-nithologist. Bartram’s detailed description is not presently endorsed by the American Ornithologists’ Union and has been widely regarded as a myth, a misdescribed King Vulture Sarcoramphus papa (Linnaeus), a misdescribed Northern Carac-ara Caracara cheriway (Jacquin), or a garbled mixture of species. In fact, his description bears almost no resemblance to a Northern Caracara, but it does match the King Vulture in all important respects except tail color (which is uniform dark brown in all ages and sexes of King Vultures but was white with a dark brown or black tip in Bartram’s description). Most 20th century ornithologists commenting on Bartram’s bird have been reluctant to accept his description because of the tail-color discrepancy. Only McAtee (1942) concluded that his description could be fully accurate as written, indicating a bird closely related to, but different from, a typical King Vulture. Paralleling Bartram’s description is an apparently independent account and painting of a vulture of uncertain geo-graphic origin by Eleazar Albin (1734). Details of Albin’s description, including tail color, are very similar to those of Bartram’s description. The only discrepancies are minor differences in color of softparts and tail that seem explicable as intraspecific variation. Available evidence suggests that Bartram knew nothing of Albin’s description, and if so, Albin’s bird provides quite persuasive support for the validity of Bartram’s bird. Equally important, none of the arguments offered historically against the validity of the Painted Vulture is persuasive when examined closely. Together, these and other fac-tors make a strong case for acceptance of Bartram’s Painted Vulture as a historic resident of northern Florida and likely other adjacent regions.